Faktor Yang Mempengaruhi Kinerja Karyawan Pada PT Samudera Indonesia - Rini Anggraini; Setyo Riyanto (Jurnal Ekonomika dan Bisnis, 2022)
Employee performance is one of the most important parts that can influence company development. Factors that affect employee performance involve the role of motivation and conditions in the environment. In this case, comfort is needed to be given to employees when carrying out the work and the responsibilities they have. The article, each employee has a different performance - different, so there is a motivation that can affect employee performance improvement. The method used in this study is a qualitative approach through interviews and observations made to company employees. The results prove that factors such as bonuses, facilities and career levels owned by employees have an influence on employee performance. Bonuses are part of the motivation that companies can provide to influence karaywan performance while career facilities and levels are work environment factors that can help improve employee performance.